Commitment and Extremism: A Goal Systemic Analysis. (9th September 2013) - Klein, Kristen M.; Kruglanski, Arie W.
Abstract : Growing evidence suggests that uncertainty is related to extremism in its various forms. The aim of the present article is to probe the underlying psychological mechanisms of this relation. We begin by considering two disparate definitions of extremism as: (1) expressed zeal/attitude polarity, and (2) deviation from a norm. Zeal constitutes a direct expression of goal commitment, whereas deviant behavior is likely to occur under high commitment because of the greater perceived instrumentality of such behavior to the goal. We discuss a psychological mechanism that implies this increased instrumentality of deviant behavior to its goal. From this perspective, the relation between uncertainty and extremism represents a special case of the general relation between goal commitment and extremism: An aversively high degree of uncertainty augments commitment to the goal of uncertainty reduction. This in turn increases the appeal of extreme expressions seen as effective ways and means to uncertainty reduction.